Advantages of plasmatic CXCL-10 as a prognostic and diagnostic biomarker for the risk of rejection and subclinical rejection in kidney transplantation - Millán, Olga; Rovira, Jordi; Guirado, Lluis; Espinosa, Cristina; Budde, Klemens; Sommerer, Claudia; Piñeiro, Gaston J.; Diekmann, Fritz; Brunet, Mercè (Clinical immunology, 2021)
This study evaluate the potential of plasmatic CXCL-10 (pCXCL-10) as a pre&post transplantation prognostic and diagnostic biomarker of T-cell-mediated rejection (TCMR), antibody-mediated rejection (ABMR) and subclinical rejection (SCR) risk in adult kidney recipients considering BKV and CMV infections as possible clinical confounder factors. Twenty-eight of 100 patients included experienced rejection (TCMR:14; ABMR:14); 8 SCR; 13 and 16 were diagnosed with BKV and CMV infection, respectively. Pre-transplantation pCXCL-10 was significantly increased in TCMR and ABMR and post-transplantation in TCMR, ABMR and SCR compared with nonrejectors. All CMV+ patients showed pCXCL-10 levels above the cutoff values established for rejection whereas the 80% of BKV+ patients showed pCXCL-10 concentration < 100 pg/mL. pCXCL-10 could improve pre-transplantation patient stratification and immunosuppressive treatment selection according to rejection risk; and after kidney transplantation could be a potential early prognostic biomarker for rejection. Clinical confounding factor in BKV+ and particularly in CMV+ patients must be discarded.
Gesehen am 21.10.2021